Comparative study of three cases where the link methodology was implemented: Rural women on the road to prosperity - Hurtado Bermudez, Jhon Jairo; Melo, Jenny; Gutiérrez Arenas, Ernesto (2016)
This publication is the result of a participatory systematization process led by the International Center for Tropical Agriculture (CIAT), on the implementation of the LINK Methodology by Heifer International on three study cases within the Rural Women on the Road to Prosperity project. This emerged within the framework of the Rural Women on the Road to Prosperity regional project, supported by Heifer International and the Ford Foundation, as well as the International Fund for Agricultural Development (IFAD) and local organizations. The project implementation started in September 2014, in Guatemala, Honduras, and Nicaragua, and it allowed for the development, implementation, validation, and adaptation of a model strategy for business development, while linking smallholders, especially women and young people, to markets.